The impact of menstrual-cycle phase on basal and exercise-induced hormones, mood, anxiety and exercise performance in physically active women - Paludo, A. C.; Cook, C. J.; Owen, J. A.; Woodman, T.; Irwin, J.; Crewther, B. T. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The influence of menstrual cycle phase on perceptual responses and exercise performance is still unclear in the literature. Therefore, this study investigated salivary estradiol (sal-E2) and cortisol (sal-C) concentrations, mood, anxiety and exercise (aerobic, anaerobic) performance in physically-active women across two menstrual-cycle phases. METHODS: Twelve women (mean age 24.9±4.3 years) were assessed in the early follicular (early-FP) and mid luteal (mid-LP) phase of their menstrual cycle. In each phase, participants were tested for both aerobic (i.e. VO2max) and anaerobic (i.e. peak power, average power and Fatigue Index) performance. Basal and exercise-induced changes in sal-E2 and sal-C concentrations, self-appraised mood and anxiety were assessed. RESULTS: We observed a significant increase in basal (pre-exercise) sal-E2 concentration from early-FP to mid-LP (P=0.05), coupled with a significant increase in VO2max in early-FP (39.9±7.8 mL/kg/min) versus mid-LP (36.9±7.8 mL/kg/min). Depression also decreased with aerobic exercise, but only in the early-FP. No other significant menstrual-phase differences in exercise performance, emotional state or hormonal change scores were identified. CONCLUSIONS: Our data suggest that physically-active women may experience a natural rise in estradiol concentration, as they transition from the early-FP to mid-LP. In the present study, this was accompanied by a small reduction in VO2max. An exercise (aerobic)-related decline in depression also emerged in the early-FP. Most of the exercise performance, emotional state and hormonal measures did not exhibit any menstrual phase-related difference.